(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The pandemic caused by CoViD-19 has highlighted all the challenges and hurdles in the protection of a fundamental human right such as the right to health in the international law, pointing to an increasingly dysfunctional scenario. The essay aims to define an interpretative scheme to describe the most relevant problems involved in the management of this global health emergency. The intent is to demonstrate that the realization of the right to health in the international legal order is delegated to juridical and organizational instruments that do not seem very functional to the protection of the population.